(untitled) (Bangladesh Journal of Infectious Diseases, 2018)
Occult HBV infection (OBI) is defined as HBV DNA detection in serum or in the liver by sensitive diagnostic tests in HbsAg negative individuals with or without serologic markers of previous viral exposure. Since OBI was first described in the late 1970s, there has been increasing concern in this topic. OBI can be both a source of virus contamination in blood and organ donations and the reservoir for full blown hepatitis after reactivation. HBV reactivation depends on viral and host factors but these associations have not been analyzed thoroughly. Although the exact mechanism of OBI yet not proved, intrahepatic persistence of viral covalently closed circular DNA under the host’s strong immune suppression of HBV replication and gene expression seems to be a cause. Current evidence suggests that OBI can favour the progression of fibrosis, cirrhosis, hepatocellular carcinoma and post transfusion hepatitis (PTH). Epidemiological data regarding the global prevalence of OBI vary due to the use of detection methods of different sensitivity and specificity. Appropriate diagnostic techniques must be adopted. Sensitive HBV DNA amplification assay is the gold standard assay for detection of OBI. Bangladesh Journal of Infectious Diseases 2018;5(1):32-38